Diversity and Use of Wild and Non-Cultivated Edible Foods in Raji Community of Karnali Province, Nepal - Yogi, Prikshya; Aryal, Kamal Prasad; Paudel, Shresty (Journal of Agriculture and Forestry University, 2026)
Our study documents wild and non-cultivated edible foods, their use, status and contribution in livelihoods of the Raji community in Bheriganga Municipality of Karnali Province Nepal. Key Informants interview, focus group discussions, field observations, and individual household surveys were conducted. The use of 74 species belonging to 52 families were identified of which 70 were angiosperms, one gymnosperm and two pteridophytes and one termite mushroom. These species were used as food, medicines, spices and for rituals and income. Among these, 26 species had multiple uses followed by 19 as fruits, 15 as vegetables and 11 as medicines. Among the frequently used vegetable species the use value of Termitomyces albuminosus was found highest (0.97) followed by Dryopteris cochleata (D. Don.) C. Chr (0.94). The informant consensus factor on medicinal plants use was found highest on cuts and wounds (0.90) followed by cough, fever and cold (0.87). Nearly 90% of the households depends for at least one month on these plants during seasons of their availability. The availability of these species has declined over time. Raji people have started in-situ conservation and domestication of some important species like Dioscorea bulbifera L., Asparagus racemosus Willd., however these resources are not given due considerations in local, provincial and national research and development programmes of government and other research institutions.